Analysis of Pencak Silat Techniques Using a Biomechanical Approach: Systematic Literature Review - Karo-Karo, Alan Alfiansyah Putra; Rahayu, Tandiyo; Setyawati, Heny; Mukarromah, Siti Baitul; Syaifullah, Rony (Physical Education Theory and Methodology, 2023)
Study purpose. The purpose of this research is to look into the use of biomechanical analysis in pencak silat martial arts techniques. Materials and methods. The PRISMA standards for systematic reviews and meta-analyses were followed in this review investigation. The study must be published within the prior five years, from January 2019 to July 2023. In the search procedure, the following keywords are used: (1) pencak silat; (2) biomechanical analysis. The search engines SINTA (Science and Technology Index) and Scopus were employed. Results. This evaluation included the results of 10 articles. Six articles looked at combat tactics, two at students and the art of movement, nine articles looked at kick attacks, and one looked at attitudes. Four articles proposed time and speed. Six articles investigated pencak silat motion angles. Conclusions. Time, angle, direction, flexion, extension, rotation, adduction, visual focus, force, moment of inertia, rotational kinetic energy, and effort are all inferred factors for pencak silat techniques.